Rhizosphere element circling, multifunctionality, aboveground productivity and trade-offs are better predicted by rhizosphere rare taxa - Wang, Puchang; Ding, Leilei; Zou, Chao; Zhang, Yujun; Wang, Mengya (Frontiers in Plant Science, 2022)
Microbes, especially abundant microbes in bulk soils, form multiple ecosystem functions, which is relatively well studied. However, the role of rhizosphere microbes, especially rhizosphere rare taxa vs rhizosphere abundant taxa in regulating the element circling, multifunctionality, aboveground net primary productivity (ANPP) and the trade-offs of multiple functions remains unknown, particularly in subtropics where data are scarce. Here, we compared the multiple ecosystem functions, the structure and function of rhizosphere soil bacterial and fungal subcommunities (locally rare, locally abundant, regionally rare, regionally abundant, and entire), and the role of subcommunities in sole and intercropping ecosystems in subtropical China. Results showed that intercropping changed multiple ecosystem functions individually and simultaneously, intercropped zea mays significantly decreased the trade-off intensity compared to sole zea mays, the trade-off intensity under intercropped Sophora davidii was significantly higher than under intercropped zea mays. Nonmetric multidimensional scaling plots and analysis of similarities showed that bacterial species, fungal species, and fungal functions in each subcommunity significantly differed among groups. Network analysis showed intercropping increased the complexity and positive interaction of rare bacteria in Zea mays rhizosphere, but decreased the complexity and positive interaction of rare bacteria in Sophora davidii rhizosphere and the complexity and positive interaction of fungi in both intercropped plants rhizosphere. Mantel test showed significant changes in species of locally rare bacteria had the strongest effect on nitrogen cycling function, ANPP and trade-offs intensity, significant changes in species of locally rare fungus had the strongest effect on carbon cycling function, phosphorus cycling function, and average ecosystem multifunctionality.